Instrumentally Inclusive: The Political Psychology of Homonationalism - Turnbull-Dugarte, Stuart J.; Ortega, Alberto Lopez (American Political Science Review, 2024)
Can nativist attitudes condition support for LGBT+ rights? The sustained advance in pro-LGBT+ attitudes in the West often contrasts with the greening of anti-immigrant sentiment propagated by nativist supply-side actors. We argue that these parallel trends are causally connected, theorizing that exposure to sexually conservative ethnic out-groups can provoke an instrumental increase in LGBT+ inclusion, particularly among those hostile toward immigration. Leveraging experiments in Britain and Spain, we provide causal evidence that citizens strategically liberalize their levels of support for LGBT+ rights when opponents of these measures are from the ethnic out-group. In a context where sexuality-based liberalism is nationalized, increasing tolerance toward LGBT+ citizens is driven by a desire among nativist citizens to socially disidentify from those out-groups perceived as inimical to these nationalized norms. Our analyses provide a critical interpretation of positive trends in LGBT+ tolerance with instrumental liberalism masking lower rates of genuine shifts in LGBT+ inclusion.
Keywords: Homonationalism; LGBT+ Right; Sexuality-based Liberalism; Political Psychology